Peran Strategis Pengacara Negara dalam Penanganan Kasus Korupsi Berdasarkan Undang-Undang Nomor 31 Tahun 1999 dalam Kerangka Negara Hukum - Yashinta Irenne Marianna; Ade Maman Suherman; Tri Setiady (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The role of State Attorneys (Jaksa Pengacara Negara, JPN) is vital in recovering state assets lost due to corruption, aligning with the principles of Indonesia’s legal state (Rechtsstaat). This study examines JPN's authority under Law No. 31 of 1999, emphasizing its dual role in civil and administrative litigation. Using a normative juridical approach, the research analyzes legal frameworks and conceptual perspectives on JPN’s functions. The findings indicate JPN’s strategic position in representing the state, not only in civil lawsuits but also in non-litigation processes for recovering state financial losses. Challenges such as limited human resources, inter-agency coordination, and protracted case resolutions hinder optimal performance. The research suggests reinforcing the institutional capacity of JPN through targeted training and promoting synergy with related agencies, such as the KPK and police. Enhancing legal competence and procedural efficiency are critical to meeting public expectations for justice and transparency in handling corruption cases.